Analisis Etika Bisnis Islam Industri Jasa Laundry Di Kecamatan Alam Barajo Kota Jambi - Eka Restu Fitri; Anzu Elvia Zahara; Ahsan Putra Hafidz (EBISMAN eBisnis Manajemen, 2024)
Islamic business ethics are ethical norms based on the Koran and Hadith which must be used as a reference by anyone in business activities. This research aims to find out how to analyze Islamic business ethics in the laundry service industry in Alam Barajo District, Jambi City. The research method used is qualitative with a descriptive approach. Primary data was obtained from laundry business owners, employees and consumers from the laundry service industry in Alam Barajo sub-district, while secondary data came from observations and archives. The findings show that the application of Islamic business ethics in the laundry service industry in Alam Barajo District, Jambi has been implemented. The majority of the laundry service industry in Alam Barajo sub-district understands Islamic business ethics as exemplified by Rasululullah in trading. For example, trusting consumer goods, maintaining quality and service to customer satisfaction so that business development can run well.